Gender differences in the impact of electoral victory on satisfaction with democracy. (February 2021) - Williams, Neil S.; Snipes, Alexandra; Singh, Shane P.
Abstract: Dozens of studies have shown that individuals who voted for the winning party in an election tend to be more satisfied with democracy than those who did not. However, a number of recent studies—many using data from the Comparative Study of Electoral Systems (CSES)—demonstrate that this relationship varies according to individual- and election-level factors. In this paper, we introduce for the first time gender as a modifier of the effect of winning on satisfaction. We advance a theoretical argument about why gender, independent of its many correlates, should shape the extent to which electoral victory induces satisfaction. Specifically, we argue that the winning effect should be smaller for women than for men because of (1) gender-based differences in political socialization and (2) gaps in the symbolic connection with candidates and parties. Given this, we also expect that the gender gap in satisfaction is moderated by women's descriptive representation. To test our expectations, we use surveys from Modules I-IV of the CSES coupled with macro-level data sources. Results indicate a robust and precisely estimated gender-based disparity in the impact of winning on satisfaction, with its magnitude being comparatively small among women. This gap is smaller where women are well represented in the legislature, though the gender of the chief executive does not play a conditioning role.